C.KHA Optimization Satpas SIM Satlantas Services of the Demak Polres to Increasing Public Satisfaction - Kharis, Muhamad (Advances in Police Science Research Journal, 2024)
The low community satisfaction index in the SIM administration unit for Demak City compared to other Polres is influenced by the not optimal indicators of community satisfaction. With issues regarding the implementation of the current service and the organizational resources of the SIM administration unit. The research objective is to provide information about existing problems and provide solutions to problem solving in accordance with the expected conditions. As well as the scope as a limitation of the author’s completion and methodology using qualitative research with the type of case study research through interview and observation data collection techniques. The research literature uses 3 types of research that have been carried out by previous police academy graduates using the concepts of optimization, security guards, driving licenses, and community satisfaction. While the factors that affect service use SWOT analysis, organizational resources use the theory of management elements, and the implementation of MIS services uses management function theory. The SIM administration administration unit is located at Jalan Kyai Singkil No.07, Petengan Selatan, Bintoro, Demak District, Demak Regency, Central Java. The mechanism used includes the service standard components contained in Law Number 25 of 2009 concerning Public Services. With sim services using the First In First Out method where applicants who arrive earlier will be served and finish early according to the applicant’s arrival time. Meanwhile, in carrying out the research, the authors found problems, namely a decrease in SIM production, the SIM practice exam field did not meet standards, the instructions for the avis test officer did not comply with the procedural provisions, did not yet have an electronic information system, lack of personnel, did not yet have mobile SIM vehicles, service personnel involved in managing VVIP guest traffic during service hours, computer infrastructure is damaged, personnel distribution is uneven, and performance appraisal is carried out by the officer concerned. With the discovery of various writer’s problems, it can be concluded that organizational resources and the implementation of SIM services are not optimal. Therefore, there is a need for problem-solving efforts and suggestions proposed by the author